Trade-off effect of polymeric nano-medicine in anti-cancer drug delivery. (December 2021) - Ma, Rujiang; Shi, Linqi
Highlights: The concept of trade-off effects of polymeric nano-medicine in anti-cancer therapy is proposed. Different trade-off effects of polymeric nano-medicine in anti-cancer therapy are summarized with emphasis on the conflict between prolonging blood circulation and enhancing cellular uptake. Tailor-made nano-carriers with charge-reversal, shell-shedding, and surface assembling abilities are discussed in detail for overcoming the trade-off effect between prolonged circulation time and enhanced cellular uptake. Abstract: Polymeric nano-medicine has been widely studied in anti-cancer therapy and great achievements have been made over the past three decades. Though side effects of drugs such as toxicity are greatly reduced, the therapeutic efficacy has not been improved significantly so far, which maybe mainly because of the trade-off effects between oppositely required functions of nano-medicines at different steps in drug delivery, such as prolonged blood circulation vs. enhanced cellular uptake, and stable drug retention in transit vs. responsive release in cancer cells. To overcome the trade-off effect between blood circulation and cellular uptake, different functionalities, including surface charge reversal, shell-shedding, and surface self-assembly properties, have been designed for nano-carriers. The starting point of these strategies is endowing the nano-carriers with stealth character during blood circulation while transforming them into a more cell-interactive state to enhance cellular uptake. This review summaries the recent advances in designing powerful nano-carriers to overcome the trade-off effect between prolonging blood circulation and enhancing cellular uptake to improve the anti-cancer therapeutic efficacy. Graphical abstract: Image, graphical abstract